2009
DOI: 10.1002/hep.23187
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase and superoxide dismutase 2 polymorphisms comodulate the risk of hepatocellular carcinoma and death in alcoholic cirrhosis #

Abstract: Alcohol increases reactive oxygen species (ROS) formation in hepatocyte mitochondria and by reduced nicotinamide adenine dinucleotide phosphate oxidases and myeloperoxidase (MPO) in Kupffer cells and liver-infiltrating neutrophils. Manganese superoxide dismutase (MnSOD) converts superoxide anion into hydrogen peroxide, which, unless detoxified by glutathione peroxidase or catalase (CAT), can form the hydroxyl radical with iron. Our aim was to determine whether Ala16Val-superoxide dismutase 2 (SOD2), G-463A-MPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 33 publications
2
73
1
Order By: Relevance
“…16 In addition, it has been shown that patients with polymorphisms of oxidant/antioxidant enzymes were at increased risk of cancer. 17 Similarly, it has been reported that the risk of HCC is higher in patients who have nonalcoholic steatohepatitis (NASH)-related cirrhosis with hepatic iron excess. 18 However, the absence of a clear association in NAFLD between iron accumulation and HFE mutations means that there is no value in assessing risk of HCC in NASH-related cirrhosis by testing for HFE mutations.…”
Section: Iron As a Cofactor In The Pathogenesis Of Hccmentioning
confidence: 99%
“…16 In addition, it has been shown that patients with polymorphisms of oxidant/antioxidant enzymes were at increased risk of cancer. 17 Similarly, it has been reported that the risk of HCC is higher in patients who have nonalcoholic steatohepatitis (NASH)-related cirrhosis with hepatic iron excess. 18 However, the absence of a clear association in NAFLD between iron accumulation and HFE mutations means that there is no value in assessing risk of HCC in NASH-related cirrhosis by testing for HFE mutations.…”
Section: Iron As a Cofactor In The Pathogenesis Of Hccmentioning
confidence: 99%
“…These genetic traits are capable of modulating several biological pathways involved in hepatocarcinogenesis, such as inflammation [63,64], oxidative stress [65,66], and iron [67,68] or lipid metabolism [69]. In this setting, other genetic modifiers of lipid turnover seem to impact HCC risk in association with PNPLA3 genotype.…”
Section: Pnpla3 In the Complex Genetic Heterogeneity Influencing Livementioning
confidence: 99%
“…6 Miscoding of Ala to Val in SOD2 will result in SOD2 arresting in the inner mitochondrial membrane but not in the mitochondrial matrix, therefore reducing its functional activities. 6 Carriage of 1 or 2 Ala-SOD2 allele(s) reportedly has been associated with greater risks of hepatocellular carcinoma, 7 gastric cancer, 8 prostate cancer 9 and a poor prognosis in breast cancer. 10 The SNP in the GSTP1 gene (rs1695) is a substitution of A (isoleucine [Iso]) to G (valine [Val]) at position 105 that results in miscoded GSTP1 protein with decreased enzymatic activity and less effective detoxification.…”
Section: Introductionmentioning
confidence: 99%